Come Scream with Me: On feminist stories and screaming into the void. Issue 3 (3rd July 2021) - Moore, Amber; Hare, Kathleen (Kaye)
ABSTRACT: In this paper, we apply a scholarly lens to 'screaming into the void, ' especially in response to similarly intense moments of lived experience as emergent feminist and literacy education scholars. Together, we produce storied soundscapes of screaming – a kind of cartography that we call feminist 'screamscapes', largely in response to our experience as cruel optimist early academics. We understand our screamscapes as feminist snaps, or breaking points, that represent us through mappings of our lived experiences – fragments of past selves that demand reflection. Presented using a co-narrative feminist inquiry where we weave our reflections and experiences together, we analyse three parts of screaming: the body screaming, the scream, and the void.